DETERMINATION OF CAPITAL STRUCTURE FACTORS: EVIDENCE FROM BUILDING CONSTRUCTION INDUSTRIES IN INDONESIA - Febria Nalurita (Business and Entrepreneurial Review, 2017)
Research has contributed to testing the Determinants of Capital Structure: Evidence from the Building Construction Industry in Indonesia, in the period 2008-2015.Secondary data used is based on time series data and cross section. Through the purposive sampling method, the total sample selected are 6 construction construction companies and used panel data regression analysis techniques that are processed with programEVIEWS 9. From the Chow test and Hausman test results show that as a data estimation technique used is the Fixed Effect model.Five independent variables in this study, which resulted in an analysis that partially profitability and liquidity had a significant effect on leverage. The results of this empirical study indicate that there is strong evidence to support the pecking order theory by building construction companies based on variable liquidity determinants of capital structure, and profitability variables are also very supportive for the trade-off theory relationship. Firm size, tangibility and non-debt tax shield have no significant effect on leverage.Together, firmsize factors, profitability, tangibility, non-debt tax shields and liquidity significantly influence the leverage of building construction companies. So, based on the trade-off theory, optimal leverage is a balance between tax benefits from debt and bankruptcy costs and agency costs incurred by the company.The sample in this study is only building construction companies so that they only have specifications in the type of business of the sample company, so the influence of the independent variables (only) only describes the specific influence in the building construction sector.